1996
DOI: 10.1103/physrevb.53.2303
|View full text |Cite
|
Sign up to set email alerts
|

Chemical damage in poly(phenylene sulphide) from fast ions: Dependence on the primary-ion stopping power

Abstract: Thin poly͑phenylene sulphide͒ foils were bombarded with fast atomic ions ͑ 4 He, 12 C, 16 O, 32 S, 79 Br, 127 I͒ in the energy range between 2.5 to 78 MeV. In order to maintain the same ion track size for all impacting ions, their initial velocity was kept constant at 1.1 cm/ns. Under these conditions the deposited energy density in a single ion track changes as a result of the varying stopping power (dE/dx) of the projectiles in the material. Fourier transform infrared spectroscopy and UV-visible spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…The radial variation of the mean deposited energy density at the time of ejection obtained here appears to be less steep than the theoretical r 22 dependence obtained for the initial energy density in the track of fast ions in a gas. This dependence is in rough agreement with recent modeling of ion tracks in polymers [25].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The radial variation of the mean deposited energy density at the time of ejection obtained here appears to be less steep than the theoretical r 22 dependence obtained for the initial energy density in the track of fast ions in a gas. This dependence is in rough agreement with recent modeling of ion tracks in polymers [25].…”
supporting
confidence: 80%
“…The effect on the velocity distributions should be small, as ͗y 2 x ͘ and ͗y x ͘ increase slowly with dE͞dx, the stopping power [24]. However, previous data on the damage cross section obtained for polymer films indicate an increase in the cross sections of up to a factor of 2 for 55 MeV I bombardments compared to 78 MeV I ions [25]. To account for these differences the radii in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4, a number of absorption peaks for SCC observed at 3,424, 2,927, 2,858, 1,576, 1,420, 1,260 and 781 cm -1 represent N-H stretching of primary aromatic amine, [CH 2 asymmetrical stretching, symmetrical stretching [CH 2 group, skeletal vibration of aromatic C=C, deformational vibration of =C-H of alkenes, C-N stretching of aromatic primary amine and -C-H out of plane deformation of aromatic compounds, respectively (Kemp 1996;Furniss et al 2005;Ghosh 2006). After treatment with thioglycolic acid, a significant decrease of these bands was noted in the spectrum of TSCC along with two new peaks at 1,702 and 1,094 cm -1 indicating C=O stretching of saturated acid (Furniss et al 2005;Ghosh 2006) and C-S axial stretching (Papaleo et al 1996) of thioglycolic acid. Moreover, the absence of the characteristic frequency at 1,420 cm -1 also shows the existence of structural disorder which has been explained as a result of chemical interaction between alkene groups of SSC and thioglycolic acid at its surface.…”
Section: Characterization Of Tsccmentioning
confidence: 99%
“…More specifically, under low <(dE/dx) e > irradiations, aromatic polymers show a very good radiation resistance, orders of magnitude higher than those of aliphatic compounds. However, it has been shown that in several aromatic polymers (polystyrene [26,27], polycarbonate [28], polyethylene terephthalate [29] and poly(pphenylene sulphide) [30,31]) that the disruption rate of chemical bonds is strongly enhanced when increasing the ion stopping power. Such effect is hence expected in BC-400 which has an aromatic polymer matrix.…”
Section: Methodsmentioning
confidence: 99%